Exact solutions for a nonstandard viscous Cahn—Hilliard system - Mchedlov-Petrosyan, P.O.; Davydov, L.N. (Доповіді НАН України, 2017)
The one-dimensional version of a nonstandard viscous Cahn–Hilliard system (proposed by Colli et al.) for the order parameter and chemical potential with a generally asymmetric polynomial double-well potential is considered. For this system, an exact travelling wave solution, which describes the advancing front of a phase transformation in an infinite domain, is found. Розглянуто одновимірний варіант нестандартної системи рівнянь Кана—Хілліарда (запропонованої Colli et al.) для параметра порядку і хімічного потенціалу з асиметричним поліномним двоямним потенціалом. Для цієї системи знайдено точне розв’язання вигляду рухомої хвилі, що описує рух фронту фазового перетворення в нескінченній області. Рассмотрен одномерный вариант нестандартной системы уравнений Кана—Хиллиарда (предложенной Colli et al.) для параметра порядка и химического потенциала с асимметричным полиномиальным двуямным потенциалом. Для этой системы найдено точное решение вида бегущей волны, которое описывает движение фронта фазового превращения в бесконечной области.